Effect of pressure on structural and elastic properties of SnSe: First-principles calculations - Phacheerak, Kanoknan; Thanomngam, Pitiporn; Limpijumnong, Sukit (My University, 2022)
Selected structural and elastic properties of an orthorhombic SnSe at an ambient pressure and under high pressures were investigated using first-principles calculations. At ambient pressure, the calculated structural parameters and elastic constants show a good agreement with previously reported values. Effects of pressure on structural and elastic properties were presented and discussed in detail. Moreover, the pressure dependence of selected structural and elastic properties, which relate to phase transition from an orthorhombic phase to the high-pressure phase, was analyzed. We suggested that the phase transition is related to the compression along the c- and b-axis which correspond to C33 and C22, respectively.
Keywords: Elastic; Phase transition; SnSe; Structural